2019
DOI: 10.3390/ma12172652
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vehicle-Induced Vibrations on the Tensile Performance of Early-Age PVA-ECC

Abstract: Polyvinyl alcohol-engineering cementitious composites (PVA-ECCs) have been widely applied in bridge deck repairing or widening, and a common practice is that a portion of the bridge is left open to traffic while the closed portion is constructed, which exposes the early-age PVA-ECC to vehicle-induced vibrations. However, whether vehicle-induced vibrations affect the performance of early-age PVA-ECC remains unknown. The purpose of this study was to conduct laboratory test programs to investigate to what extent … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
(50 reference statements)
3
3
0
Order By: Relevance
“…In the hardening segments, the flexural loads of the specimens increased slowly with the increase in the corresponding deflection, and the segments presented significant deformation-hardening or strain-hardening characteristics, indicating that vibrations that occurred during different setting periods have no significantly negative impact on the inherent strain-hardening behavior of PVA-ECCs under the operating conditions for Var. 1.The above results are consistent with the tensile stress–strain curves of NP-ECC-BRs that were obtained under the same experimental and parametric conditions in [29].…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…In the hardening segments, the flexural loads of the specimens increased slowly with the increase in the corresponding deflection, and the segments presented significant deformation-hardening or strain-hardening characteristics, indicating that vibrations that occurred during different setting periods have no significantly negative impact on the inherent strain-hardening behavior of PVA-ECCs under the operating conditions for Var. 1.The above results are consistent with the tensile stress–strain curves of NP-ECC-BRs that were obtained under the same experimental and parametric conditions in [29].…”
Section: Resultssupporting
confidence: 90%
“…These above results regarding the flexural load-bearing capacity obtained in this section was similar to that of the ultimate tensile strength of NP-ECC-BRs in [29], as well as the compressive strength, bond strength, splitting tensile strength, and flexural strength of NP-C-BRs when vibrations occurred only during the setting period [22,23,24]. The results in [22,23,24,29] showed that the TRVs that occurred only during the setting periods affected the performance of NP-C-BRs or NP-ECC-BRs to some extent which should not be ignored.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations